2013
DOI: 10.1063/1.4773579
|View full text |Cite
|
Sign up to set email alerts
|

Combined crossed beam and theoretical studies of the C(1D) + CH4 reaction

Abstract: The reaction involving atomic carbon in its first electronically excited state (1)D and methane has been investigated in crossed molecular beam experiments at a collision energy of 25.3 kJ mol(-1). Electronic structure calculations of the underlying potential energy surface (PES) and Rice-Ramsperger-Kassel-Marcus (RRKM) estimates of rates and branching ratios have been performed to assist the interpretation of the experimental results. The reaction proceeds via insertion of C((1)D) into one of the C-H bonds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 56 publications
4
52
0
Order By: Relevance
“…We have performed RRKM calculations using the same code developed by us and described in previous papers [41,42]. The microcanonical rate constant for each elementary step is calculated using the formula kðEÞ ¼ NðEÞ=hqðEÞ where N(E) denotes the sum of states in the transition state at energy E, q(E) is the reactant density of states at energy E and h is Planck's constant.…”
Section: Rrkm Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed RRKM calculations using the same code developed by us and described in previous papers [41,42]. The microcanonical rate constant for each elementary step is calculated using the formula kðEÞ ¼ NðEÞ=hqðEÞ where N(E) denotes the sum of states in the transition state at energy E, q(E) is the reactant density of states at energy E and h is Planck's constant.…”
Section: Rrkm Calculationsmentioning
confidence: 99%
“…In particular, we have used the M06L local density functional method [41]. Restricted calculations were used for closed-shell systems and unrestricted ones for open-shell systems.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…We obtained rate constants via a combination of capture theory and RRKM calculations, using the same code we developed and described in previous papers (Leonori et al 2009(Leonori et al , 2013Balucani et al 2015). The rate constant for the formation of the initial intermediate is calculated using capture theory as detailed in Vazart et al (2015).…”
Section: Kinetics Calculationsmentioning
confidence: 99%
“…For instance, a beam characterization via Stern-Gerlach magnetic analysis has revealed that a significant fraction of atomic oxygen and nitrogen are formed in their 1 D and 2 D, respectively, electronically excited metastable states, while a fraction of atomic chlorine is formed in the excited spinorbit state, 2 P 1/2 (Alagia et al 1997). We have obtained experimental evidence that also atomic carbon and sulfur are partially formed in their first electronically excited 1 D states (Leonori et al 2008a;Leonori et al 2009). In this way, we have been able to investigate the dynamics of several reactions involving these excited species, with some of them being relevant in the chemistry of planetary atmospheres and cometary comae.…”
Section: Beam Production and Characterizationmentioning
confidence: 92%
“…2 Electron ionization efficiency as a function of electron energy of the HCCS radical product from the S( 1 D) ? C 2 H 2 reaction at E c = 35.6 kJ mol -1 (adapted, with permission, from Leonori et al 2009) reactants requires sources specifically devised for their generation starting from precursor species. Among the various techniques, in our laboratory we make use of a high-pressure, high-power radio frequency (RF) discharge source (Alagia et al 1997).…”
Section: Beam Production and Characterizationmentioning
confidence: 99%